1991
DOI: 10.1111/j.1432-1033.1991.tb16483.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity and conformational transition of α1‐proteinase inhibitor variants

Abstract: Several variants of al-proteinase inhibitor (al-PJ) were investigated by spectroscopic methods and characterized according to their inhibitory activity. Replacement of Thr345 (P14) a,-Proteinase inhibitor (al-PI) is a member of the serine proteinase inhibitor (serpin) family [l -41. Inhibitors of this class play crucial roles in controlling proteolytic activities of major physiological importance, such as in coagulation, fibrinolysis and complement activation [5]. Several studies provided evidence that serpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 30 publications
4
33
0
Order By: Relevance
“…For instance, the equilibrium unfolding transition of inhibitory serpins including ␣ 1 AT (Fig. 2) is very complex (5,(27)(28)(29), whereas the unfolding transition of ovalbumin is more or less fitted to a two-state model when monitored either by far UV CD signal (5), intrinsic fluorescence (30), or by UV absorbency and intrinsic viscosity (31). The unfolding midpoint of C73A mutant ovalbumin, which could not form disulfide bonds, was very close to that of Multi-7 ␣ 1 AT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the equilibrium unfolding transition of inhibitory serpins including ␣ 1 AT (Fig. 2) is very complex (5,(27)(28)(29), whereas the unfolding transition of ovalbumin is more or less fitted to a two-state model when monitored either by far UV CD signal (5), intrinsic fluorescence (30), or by UV absorbency and intrinsic viscosity (31). The unfolding midpoint of C73A mutant ovalbumin, which could not form disulfide bonds, was very close to that of Multi-7 ␣ 1 AT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We used a non-inhibitory PAI-1 mutant, PAI-1 R , which carries two arginyl residues at positions 333 and 335 in the proximal hinge, corresponding to RCL residues P12 and P14, but is otherwise identical to wtPAI-1 in primary amino acid sequence (23). Bulky charged residues at the proximal hinge have been shown to slow the insertion of the RCL into ␤-sheet A (45,46). Thus PAI-1 R behaves as a substrate and is completely cleaved by target proteases.…”
Section: Pai-mentioning
confidence: 99%
“…Based on studies of naturally occurring mutants of the Cl inhibitor, Skriver et al [50] showed further effects also involving the P12 and PlO sites. Finally, since a major pathway for aggregation involves the complexation of strand s4A of one molecule in sheet A of another, aggregation studies also provide structural information [ 12, 15,48,49] and additionally demonstrate the mechanism of a type of serpin deficiency mutant syndrome.…”
Section: Experimental Clues To Conformational Properties the Occurrenmentioning
confidence: 99%